(untitled) - Leistner, Lothar (New York, 2002)
Hurdle Technologies: Combination Treatments for Food Stability, Safety and Quality is the first work on hurdle technology in which all aspects, the possibilities and limitations of hurdle technology, are comprehensively outlined and evaluated. World-renowned on the subject, Leistner and Gould were instrumental in the development of the hurdle technology concept and in the last decades have obtained much practical experience in the application of this successful approach in the food industry worldwide.
Keywords: Thực phẩm,Food; Bảo quản,Preservation